Perancangan Spesial Tools Rebusihng Torq Rod dan Radius Rod HD7857 - Yasya Khalif Perdana saleh; Faiza Ariq Muhammad; Inyoman Jujur; Luqman, muhammad Luqman Saiful Fikri; Mohamad Zaenudin (Universitas Nusa Putra, 2025)
Mining activities require regular maintenance of heavy equipment to ensure operational reliability. This study aims to design a special tool to support the rebushing process for the Torq Rod and Radius Rod of the HD7857 unit, enhancing work efficiency and quality. The research method includes interviews, needs analysis, and simulations using the Finite Element Analysis (FEA) method. The design results indicate that the tool can withstand pressure up to 600 bar (420 kN), with a maximum stress of 402.6 MPa, a safety factor of 1.14, and deformation within elastic limits. However, it is recommended to limit the pressure to 500 bar to maintain tool reliability. This tool design is expected to reduce errors in bushing installation, standardize work quality, and minimize unit downtime. The study contributes to the development of heavy equipment maintenance tools and can serve as a reference for similar future research